A high sensitivity HI survey of the sky at δ ≤ -25° - Arnal, Edmundo Marcelo (2000)
This paper reports on a high sensitivity λ 21-cm neutral hydrogen survey of the sky south of δ ≤ -25°. A total of 50980 positions lying on a galactic coordinate grid with points spaced by (Δl, Δb) = (0°.5/cos b, 0°.5), were observed with the 30 m dish of the Instituto Argentino de Radioastronomía (IAR). The angular resolution of the survey is HPBW = 30′, and the velocity coverage spans the interval -450 km s-1 to +400 km s-1 (LSR). The velocity resolution is 1.27 km s-1 and the final rms noise of the entire database is ∼ 0.07 K. The brightness temperature scale is accurate to 5%.